The Decembrist Revolt of 1825 as a Tool to Assess the Modern Russian Call for Freedom: The Case of the Russian Protests of 2011-2012 - Ande, Vera (Student Undergraduate Research E-journal!, 2016)
The article presents a comparative historical analysis of two events from the Russian history: The Decembrist Revolt of 1825 and the Russian uprising of 2011-2012. The analysis is aimed at defining features that both events have in common. Based on the aftermath of the Decembrist revolt, the implications of the Russian uprising of 2011-2012 for the Russian domestic politics in the long-run are foreseen. The study uses a multidisciplinary and holistic approach, covering political, socio-cultural, and economic perspectives. After a general description of both events the comparison takes place, followed by the conclusion.